LITERASI MATEMATIS MAHASISWA DALAM MENGERJAKAN MASALAH KONTEKSTUAL MATEMATIKA - Muhammad Rizaldi; Pantur Pandiangan; Muhamad Hamdani (JURNAL PENDIDIKAN, 2023)
Mathematical literacy or usually known as numeracy is an interesting educational topic because it is one of the competency standard criteria for graduates. The purpose of this research is to describe students' mathematical literacy in working on contextual mathematic problems. This research method is descriptive qualitative research which the instruments are tests of mathematical literacy skills and interviews. This research was conducted on 3rd semester mathematics education students. Result of this research is description of the subjects that has the best mathematical literacy among the others. Students who have good mathematical literacy when working on contextual problems will identify and create the variables needed for the initial step of solving the problem. Then he can use concepts, facts, procedures, and mathematical reasoning by using the variables he has created and connecting them with the his knowledge. Finally he also interprets, applies, and evaluates the results mathematically by providing conclusions from the solutions he has worked on.